HUKUM DAN MORAL: MENGULIK ULANG PERDEBATAN POSITIVISME HUKUM DAN TEORI HUKUM KODRAT H.L.A HART & LON F. FULLER - Rusydi, Muhammad (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2021)
ABSTRACT This paper explores the theoretical exchange between two influential legal thinkers, H.L.A. Hart and Lon F. Fuller. The first mentioned represent the school of legal positivism while the later known as the defender of natural law theory. This paper refers to their early works of Hartâ€™s â€œPositivism and the Separation of Law and Moralsâ€ and Fullerâ€™s â€œPositivism and Fidelity to Law-A Reply to Professor Hartâ€ which both published in 1958. Keywords: Legal Positivism, Natural Law Theory, H.L.A. Hart, Lon F. Fuller.